Media Competence as a Cross-curricular Competence - Kačinová, Viera (Communication Today, 2018)
The aim of the study is to demonstrate the cross-curricular character of media competence developed in the process of media education that is integrated into the content of school education in accordance with the prevailing current international curriculum trends and with emphasis on the Slovak curriculum. In terms of comparing the conditions during the period of incorporation of media education as a compulsory part of the content of Slovak education system with the contemporary innovated form of the curriculum, the study mainly presents which school subjects are instrumental in developing the dimensions of media competence of students, especially within complete secondary general education, and how they participate in the development. The key aim is to investigate the problem on the basis of a qualitative content analysis of innovated learning standards of compulsory subjects, specifically for the level of upper secondary education (grammar schools), with the intention of identifying the required quality of media competence within the specified educational objectives. Minding the determined categories of the content analysis, a theoretical activity-based media-competency model is applied with the main dimensions as follows: getting to know media and their products; critical evaluation and taking a value stand on media products; media products creation and dissemination, and the derived main educational objectives. The model includes the current key framework activity categories stimulating the required development of media competence or literacy in the context of Slovak educational policy.